Toward a grounded theory of nursing student attrition - Cook, Lenora, author; Davies, Timothy Gray, 1942-, advisor; Bundy-Fazioli, Kimberly, committee member; Kuk, Linda, committee member; Carlson, Laurie A., committee member (Colorado State University. Libraries, 2010)
Attrition of students from a nursing program is a significant concern. It is even more critical now because there are not enough nurses to fill all open positions in the healthcare industry. It is predicted the shortage will worsen in the next decade as an aging society increases the number of people requiring nursing care. While increasing the number of students admitted to nursing programs has been a popular method to meet this demand, finding ways to retain students in nursing programs would also increase the number of nurses entering the profession. Understanding attrition is the first step in developing retention programs. This grounded theory study of attrition from the student's point of view provided insight on the phenomenon of nursing student attrition. Data were obtained through in-depth interviews of individuals who had left a community college nursing program for a semester or more, returned, and successfully completed a community college nursing program. These nurses provided a rich source of data because they had a unique perspective of attrition and successful completion. The grounded theory process provided a systematic approach to data collection, analysis, and synthesis of data leading to the emergence of four axial categories and one core category. This study describes and explains the interaction of the axial categories of caring, courage, control, and adaptation. These intricate and entwined categories make up the core category of psychic strength. The findings of this study indicate that students enter nursing programs with varying levels of psychic strength. The challenges and stress of nursing school create anxiety that weaken psychic strength. In most cases students were able to adapt and regain homeostasis. If they were unable to adapt, they felt powerless. This feeling of powerlessness increased their level of anxiety. The cyclical process of challenges and adaptation leads to personal growth. If students are not able to adapt and regain control, they may lose courage to continue in school. These factors weaken or fracture psychic strength. This study provides insight on nursing student attrition in community college nursing programs. Understanding how psychic strength can be weakened and lead to attrition will be useful to nurse educators searching for retention strategies.
Department Head: Carole J. Makela.